2012
DOI: 10.1093/cid/cis372
|View full text |Cite
|
Sign up to set email alerts
|

Severe Outcomes Are Associated With Genogroup 2 Genotype 4 Norovirus Outbreaks: A Systematic Literature Review

Abstract: Our review suggests that hospitalizations and deaths were more likely in outbreaks associated with GII.4 viruses, independent of other factors, and underscores the importance of developing vaccines against GII.4 viruses to prevent severe disease outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 20 publications
10
109
1
2
Order By: Relevance
“…Our results are comparable to the 0·03% in longterm care facilities in Australia [22] and the 0·07% described in a review of published outbreaks [20], considering that our dataset includes sporadic cases that are younger and less likely to develop complications. Our mortality rate of 0·5/100 000 cases per season in the elderly (575 years) is lower than modelling estimates from the USA, UK and The Netherlands of 2/100 000, 0·6/100 000 and 3/100 000, respectively 8 11 2 5 8 11 2 5 8 11 2 5 8 11 2 5 8 11 2 5 ll.4 all ll.2 ll.7 Gll other Gl all GII recomb [3,23,24], but comparable when considering that the surveillance system captures only half of norovirusassociated deaths compared to the German causeof-death statistics [25].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results are comparable to the 0·03% in longterm care facilities in Australia [22] and the 0·07% described in a review of published outbreaks [20], considering that our dataset includes sporadic cases that are younger and less likely to develop complications. Our mortality rate of 0·5/100 000 cases per season in the elderly (575 years) is lower than modelling estimates from the USA, UK and The Netherlands of 2/100 000, 0·6/100 000 and 3/100 000, respectively 8 11 2 5 8 11 2 5 8 11 2 5 8 11 2 5 8 11 2 5 ll.4 all ll.2 ll.7 Gll other Gl all GII recomb [3,23,24], but comparable when considering that the surveillance system captures only half of norovirusassociated deaths compared to the German causeof-death statistics [25].…”
Section: Discussionsupporting
confidence: 86%
“…GII.4 strains have been reported to cause more severe illness [20,27] and a higher viral load in infected persons than other strains [28], which may lead to more frequent disease transmission. A higher environmental stability has also been discussed [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although it often causes a brief and self-limited illness, among vulnerable populations, such as elderly people or individuals who are immunosuppressed, NoV illness can be more protracted and have severe outcomes [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Within the genotypes, GII.4 is the most prevalent worldwide (Zakikhany et al 2012;Kim et al 2013;Maritschnik et al 2013). The GII.4 strains evolve through serial changes in the VP1 sequence, which allows evasion of immunity in the human population (Siebenga et al 2009) and the observed increase in the number of outbreaks has coincided with the emergence of novel variants (Desai et al 2012; Centers for Disease Control and Prevention (CDC) 2013).…”
Section: Introductionmentioning
confidence: 99%